The Study Of Domestic Violence And The Impact On Children In Malaysia - Noor ‘Ashikin, Hamid; Kamaliah, Salleh; Noraida, Harun; Asiah, Bidin (2017)
Due to exposure to numerous forms of abuse and violence at home, children who are being brought up in such surroundings experience continuous and extensive worry, anxiety and fear. The impact of the exposure and experience on the children can be disastrous which could eventually affect their health and wellbeing in their life journey towards their maturity and adulthood. This paper is written to examine appropriate solutions in controlling the occurrence of the crime of domestic violence against women which has impact on children. The paper focuses on understanding the concept of the domestic violence, investigating the various steps taken to overcome the problems as well as analysing the impact of this crime on children. The methodology used in order to achieve the above objective is qualitative in the form of descriptive study. It was found in domestic violence cases, children are often the forgotten victims. In reality, children in most cases were exposed to escalated levels of violence inflicted by one of their parents on the other.